Child deprivation in Australia: A child‐focused approach. Issue 1 (25th March 2019) - Saunders, Peter; Brown, Judith E.; Bedford, Megan; Naidoo, Yuvisthi
Abstract: Income‐based studies of child poverty treat children and young people as effectively invisible and determine the poverty status of families or households on the basis of information that is provided by, and is primarily about, adults. In contrast, the consensual deprivation approach provides a way of developing measures that reflect the views of children about what constitutes poverty and can be applied to data that children themselves provide. This paper extends earlier Australian studies of adult deprivation by applying a similar approach to children aged 11–17 attending a NSW government high school. Focus groups were conducted with children to help identify items regarded as essential for all children, and the results informed the development of a survey that was completed by over 2, 600 students. The survey asked about 24 items, 18 of which were retained after statistical testing, and these items form the basis of the deprivation analysis. The findings indicate that a substantial proportion of survey respondents experience either or both of material deprivation and social exclusion. A new Child Deprivation Index (CDI) is developed and used to compare the circumstances of different groups, highlighting some of the factors that are associated with higher levels of deprivation and providing some initial pointers to possible underlying causes.